ANALYSIS OF CUSTOMER SATISFACTION ON THE MARKETING MIX OF GOFOOD SERVICES IN PEKANBARU CITY - Deby Kurnia; Taufik Setiawan (Indonesian Journal of Agricultural Economics, 2022)
Competition between service providers is getting stronger, demanding the availability of appropriate service marketing mix strategies that must be adapted to the characteristics and tastes of various people. This study aims to examine the marketing mix implemented by Gofood in Pekanbaru City and its impact on the level of consumer satisfaction. The research method used is survey research using a non-probability sampling technique, which then uses the Customer Satisfaction Index (CSI) to analyze the level of consumer satisfaction with Gofood's service marketing mix in Pekanbaru City. Based on calculations, the acquisition of the CSI value from the marketing mix of Gofood services is 0.81, which means consumers are very satisfied with the performance of the marketing mix of Gofood services. Gofood services are expected to be able to maintain their achievements on attributes whose performance is considered good by consumers so that they can maintain consumer loyalty to Gofood services. Some of the main attributes are outlet completeness, complaint service, important information display design, easy-to-understand information display design, widespread information on promotional activities, easy-to-understand promotional messages, attractive promotions, easily accessible services, and easy-to-obtain services